Pleomorphic adenoma of parapharyngeal space: a rare case report - Peruvaje, Vijay; Narasappa, Yogesh Bandiahanapalya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Parapharyngeal space is one of the potential facial planes for neoplasms representing less than 1% of all head and neck tumours, often pose therapeutic and diagnostic problems due to variable nonspecific symptoms and the complex anatomy of the space and tend to delay the diagnosis resulting in poor prognosis. We here with report a 21 years old female patient, who presented with change in voice and swelling in right submandibular area. On examination of oral cavity, a smooth firm bulging mass was seen in the right tonsillar and para-tonsillar region with medialisation of right tonsil. Contrast enhanced computed tomography showed minimally enhancing encapsulated soft tissue density mass in right parapharyngeal space. Patient underwent excision through transcervical approach. Histopathology of the specimen showed pleomorphic adenoma. No evidence of recurrence till date.